A Novel Encochleated Formulation Improves Atovaquone Activity in a Murine Model of Pneumocystis Pneumonia. (27th November 2020) - Cushion, Melanie T; Kumar, Parag; Lu, Ruying; Ashbaugh, Alan; Adeojo, Lilian W; Alfaro, Raul; Mannino, Raphael; Tramont, Edmund; Kovacs, Joseph A
Abstract: Although atovaquone is effective in treating and preventing Pneumocystis pneumonia (PCP), its use is limited by nonlinear absorption and adverse events. The current study was undertaken to examine the activity of encochleated atovaquone (eATQ), a novel lipid-crystal nanoparticle formulation, in a mouse model of PCP. eATQ 100–200 mg was superior to commercially available atovaquone at 14 days in decreasing total Pneumocystis nuclei and asci. eATQ plus anidulafungin reduced nuclei significantly better than commercial atovaquone plus anidulafungin. eATQ is a novel formulation of atovaquone that warrants further evaluation for treatment and prevention of PCP. Abstract : In a mouse model of Pneumocystis pneumonia, a novel encochleated nanoparticle formulation of atovaquone was superior to commercially available atovaquone in clearance of infection when each drug was administered alone as well as when combined with anidulafungin.